MeinProf.de und die Qualität der Lehre - Klaus Beckmann; Andrea Schneider (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
This paper compares student evaluation of teaching on the web site MeinProf.de to the standard evaluation procedures at German universities. While MeinProf offers the advantage of a broad, publicly available database, a number of theoretical and econometric problems emerge. Many of these problems are, however, pervasive in the student evaluation of teaching as a whole. We demonstrate that this seriously hampers empirical work on the relationship of teaching and research.
urn:nbn:de:gbv:705-opus-19251
Keywords: I20; I23; 330; Lehrevaluation; Lehre versus Forschung; Lehrqualität; Hochschullehrer; Bewertung; Internet; Studium; Dienstleistungsqualität; Deutschland